Pengembangan Sarana dan Tekhnologi Pembelajaran Interaktif di MTsS Nurul Iman, Tanjung Morawa, Kabupaten Deli Serdang, Provinsi Sumatera Utara - Nasution, Harris Pinagaran; Nursiah; Novita, Vivianti; Purnami, Suri (Politeknik Negeri Medan, 2024)
learning system development begins with improving the quality of facilities and infrastructure that support learning activities. Very different from the learning system that still seems traditional. Learning facilities are everything that supports the smooth running of the learning process. With various school learning facilities and infrastructure available, their use can support learning activities. Educational facilities are a tool that supports children in the learning process. Learning media facilities are one of the facilities for teachers to transfer information from teachers to students. MTS Nurul Iman, Tanjung Morawa, is one of the foundations in child welfare and Islamic education, which aims to make the nation's children intelligent. However, the condition is still lacking in the development of learning technology, which can hamper children's learning process. Children's learning process at MTsS Nurul Iman, Tanjung Morawa, is still conventional, and only a few classes use projectors and portable screens, which should be used as learning support media.